Migración de data center – Sector Andinos - Herbozo Girón, César Joel (2018)
The company in which this project has been developed is a global food and beverage corporation with presence in more than 200 countries, their products have a very high percentage of participation in all the present markets, and with important strategic alliances with entertainment companies. This project was born as a global initiative in which the main objective was to improve the quality of IT services, to achieve this goal, it was established as an action to change our Datacenter provider, choosing HCL as a future supplier and ending Current contracts with HP. This project was carried out in all sectors of PepsiCo at a global level, and in the LATAM sector, Andean region in particular, we took the project together with the local Compute team, and we considered that this was the perfect opportunity, not only to consolidate our Datacenter (distributed in Bogota, Lima and Monterrey), but also to generate an internal order in terms of the number of servers and databases, so we created as an internal initiative to the migration project the reordering also, this initiative would aim to further improve the quality of service offered by the IT team, thus reducing the high number of incidents and discontent that the organization had for these services, in addition to that we would generate even more savings than projected, given that numbers of servers, databases, licenses, etc. This project was considered a success case in the organization and the participating team was awarded in the BEST OF IT category, highlighting the determination, identification of opportunities and professional level that the team had for this project.